2019
DOI: 10.22270/jddt.v9i6-s.3766
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Medication Errors in a Tertiary Care Teaching Hospital: A Prospective Observational Study

Abstract: Background: Medication error is defined as any avertable event that may cause or lead to inappropriate medication use or patient harm while the medication is in the control of the health care professional, patient and consumer. Medication errors may occur at any stage of the medication use process including ordering, transcription, dispensing, administering and monitoring.  Objective: The objective of the study is to assess the medication errors in a tertiary care hospital and to categorize them based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Other results showed that from 2742 drugs prescribed in India, antibiotics contributed 26.8% of the medication errors recorded in a government hospital. From the results, hospitals need to compile related policies for better antibiotics prescription [5]. An American study stated that group antibiotics aminoglycosides utilization is very potential in causing hearing disorder side effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Other results showed that from 2742 drugs prescribed in India, antibiotics contributed 26.8% of the medication errors recorded in a government hospital. From the results, hospitals need to compile related policies for better antibiotics prescription [5]. An American study stated that group antibiotics aminoglycosides utilization is very potential in causing hearing disorder side effects [6].…”
Section: Introductionmentioning
confidence: 99%